Determination of benzene series compounds and chlorobenzenes in water sample by static headspace gas chromatography with flame ionization detection. Issue 11 (15th May 2015) - Hu, Hongmei; Li, Tiejun; Sun, Xiumei; Zhang, Xiaojun; Zhang, Xiaoning; Zhong, Zhi; Guo, Yuanming
<x xml:space="preserve">Abstract</x> A simple, efficient, solvent‐free, and readily commercially available approach for the determination of eight benzene series compounds and 12 chlorobenzenes in water samples using the static headspace sampling and gas chromatography with flame ionization detection has been described in this paper. The proposed static headspace sampling method was initially optimized, and the optimum experimental conditions explored were 10 mL water sample containing 20% w/v sodium chloride placed in a 20 mL vial and stirred at 70°C for 43 min. The linearity of the method ranged from 1 to 200 μg/L for 20 analytes, with correlation coefficients ranging between 0.9962 and 0.9994. The limits of detection were in the μg/L level, ranging between 0.15 and 0.4 μg/L. The relative recoveries of spiked benzene series and chlorobenzenes with external calibration method at different concentration levels in pure, tap, and sea water samples were 84–113, 78–115 and 85–119%, respectively, with relative standard deviations of 3.8–6.8, 4.1–5.8, and 4.8–5.4% (n = 5), respectively. That this method can be successfully applied to the determination of benzene series compounds and chlorobenzenes in pure, tap, and sea water samples, simultaneously.